Modellprädiktive Vorsteuerung für einen kinematisch redundanten hybridkinematischen Mechanismus im Industrieumfeld - Rüting, Arne Thorsten; Block, Eduard; Trächtler, Ansgar (Fachtagung Mechatronik 2017)

Innovative Suspensions for Caterpillar Vehicles - Poddubny, Wladimir; Trächtler, Ansgar; Warkentin, Andreas P.; Krüger, Martin (Russian Engineering Research)

Methodology for Determining Critical Locations in Road Networks based on Graph Theory - Henning, Sven; Biemelt, Patrick; Abdelgawad, Kareem; Gausemeier, Sandra; Trächtler, Ansgar (IFAC World Congress 2017)

Sliding-Mode-Regler zur Kraft- und Positionsregelung eines Formgedächtnislegierung-Aktors - Pai, Arathi (Regelungstechnisches Kolloquium)

Scientifc Automation: Hochpräzise Analysen direkt in der Steuerung - Papenfort, Josef; Bause, Fabian; Frank, Ursula; Strughold, Sebastian; Trächtler, Ansgar; Bielawny, Dirk; Henke, Christian (Wissenschaftsforum Intelligente Technische Systeme (WinTeSys))

Reliable Multipath Communication Approach for Internet-based Cyber-physical Systems - Elattar, Mohammad; Jasperneite, Jürgen; Trächtler, Ansgar; et, al (26th IEEE International Symposium on Industrial Electronics (ISIE))

Flachheitsbasierte Positionsregelungen für Parallelkinematiken am Beispiel eines hochdynamischen Hexapoden - Knoop, Sarah

Mechanisch - mathematisches Modell eines Kettenfahrzeuges für die Entwicklung innovativer Antriebs- und Federungssysteme (auf russ.) - Poddubny, Wladimir; Trächtler, Ansgar; Warkentin, Andreas P.; Krüger, Martin (Interbranch Scientific and Technical Magazine «Vestnik Mashinostroeniya»)

Rational Decision-Making for the Beneficial Application of Additive Manufacturing - Deppe, G.; Koch, R.; Kaesberg, M. (28th Annual International Solid Freeform Fabrication Symposium)
Additive Manufacturing is a technology that offers a high potential forindustrial companies.Nevertheless, companies lack experience with this new technology and face the problem to identify processes where a successful and beneficial application can be achieved. They have to be supported in this analysis with a decision support tool which is capable to compare different manufacturing or repair approaches in order to determine the optimal solution for the correspondent use case. This is not always driven solely by costs but can also be critically affected by further influencing factors. This is why the decision support takes into account also time and quality alongside the costs. For a time-critical spare part supply, for example within aerospace sector, they are substantial for taking a decision. The presented decision support features a multi-attribute decision-making approach for selecting the most appropriate process, either Additive Manufacturing, conventional technologies or an external procurement.

Computer integration for geometry generation for product optimization with Additive Manufacturing - Reiher, T.; Vogelsang, S.; Koch, R. (28th Annual International Solid Freeform Fabrication Symposium)
Designing parts for additive manufacturing (AM) offers a broad range of geometrical and functional potentials. On the one hand the manufacturingtechnology offers the possibility of manufacturing highly complex freeform shapes, often referred to as bionic shapes. By use of these, perfect force fluxes without stress risings due to imperfect notches are realizable, getting the most value of used material. On the other hand these complex structures require a reliable geometry representation in compatible CAD-files. Conventional CAD systems were developed to generate geometries that are manufacturable with conventional machining. These are not capable of representing the high complex designs for AM. Especially for geometries generated by CAE like from topology optimization the conventional CAD systems fail to take advantage of the combination of CAE and AM. This paper explains why there is a lack of compatibility of well-known CAD systems with the potentials of AM. Therefore the AM-side of the problem is described by showing some potentials of AM and the need of high complex structures for this manufacturing technology. For the other side of the problem conventional methodologies for geometry representation of CAD systems are described and their limitations with regard to AM are worked out. Finally a voxel based geometry representation is presented as a solution for computer aided geometry generation of high complex AM–structures.

Integrating AM into existing companies - selection of existing parts for increase of acceptance - Kruse, A.; Reiher, T.; Koch, R. (28th Annual International Solid Freeform Fabrication Symposium)
In many branches in the designengineerdepartment, product designs are just variations of existing parts. To bring the additive manufacturing technology closer to the Designer, it is necessary to show them which of their existing, conventionally manufactured parts can be produced with this technology. Apartselection methodology supportsdesigners in the decision whether a part is suitable for additive manufacturingor not. Due to the potential of the technology, which was especially seen in the aerospace industries, many criteria of the methodology were initially adapted for this industry. Furthermore the methodology is based on a quantified weighting system, which comes to a certain subjectivity. For future use, a development towards a less subjective methodology should be accomplished. Through a more detailed adaption for individual industries and a simplification of the input mode, the objectivity of the criteria can be increased. Likewise, the input time can be reduced by simplifying the questioning. A more efficient part selection will be achieved by a better weighting system.In the BMBF project “OptiAMix” this methodology is supposed to be further developed for highly different branches. By a better weighting system, the part selection will be more efficient. Therefore,the willingness for the use of the improved selection andfor the additive manufacturing technology will be increased.

Design for protection: Systematic approach to prevent product piracy during product development using AM - Jahnke, U.; Koch, R.; Oppermann, A. T. (28th Annual International Solid Freeform Fabrication Symposium)
Although infringements of intellectual properties in terms of product piracy are growing for years and threaten investments in research and development most companies still rely on legal measures like property rights. A more preventive effect to protect against counterfeits can be achieved using technical measures complicating reverse engineering, improving traceability and assuring data protection. Additive Manufacturing can contribute a lot to the effectivity and efficiency of those technical measures but presently they are often unconsidered during product development. To support decision makers and designers through all the steps of a product development process an integrated systematic approach has been developed. Protective measures using AM are allocated to specific process steps and responsible persons in charge so that the result is a guideline for “design for protection”. The main idea is to help developing piracy-robust products for that the return of investment is not threatened by counterfeits and its economical impacts.

Ramp-Up-Management in Additive Manufacturing – Technology Integration in existing Business Processes - Büsching, J.; Koch, R. (28th Annual International Solid Freeform Fabrication Symposium)
In conventional manufacturing, ramp-up-management describes the planning and organization of the period between finished product development and the achievement of full production capacity for defined products. This classification has to be adapted and restructured by means of product independent and tool-free production in additive manufacturing. Therefore ramp-up-management already starts with decisions on the extentof the use of additive manufacturing, includes the building of technology-know-how as well as the technology integration into processes and infrastructure of the company and ends with the attainment of a sufficient process reliability for the AM-machine. This paper focuses on technology integration in processes and infrastructure, which is part of the German research project OptiAMix. In this project, new systems for process state analysis adapted to additive manufacturing and methods for the optimal integration of additive manufacturing are developed. Furthermore ways of using the synergies of existing infrastructures and new innovative production technologies are determined.

Computer integration for geometry generation for product optimization with Additive Manufacturing - Reiher, T.; Vogelsang, S.; Koch, R. (28th Annual International Solid Freeform Fabrication Symposium)
Designing parts for additive manufacturing (AM) offers a broad range of geometrical and functional potentials. On the one hand the manufacturingtechnology offers the possibility of manufacturing highly complex freeform shapes, often referred to as bionic shapes. By use of these, perfect force fluxes without stress risings due to imperfect notches are realizable, getting the most value of used material. On the other hand these complex structures require a reliable geometry representation in compatible CAD-files. Conventional CAD systems were developed to generate geometries that are manufacturable with conventional machining. These are not capable of representing the high complex designs for AM. Especially for geometries generated by CAE like from topology optimization the conventional CAD systems fail to take advantage of the combination of CAE and AM. This paper explains why there is a lack of compatibility of well-known CAD systems with the potentials of AM. Therefore the AM-side of the problem is described by showing some potentials of AM and the need of high complex structures for this manufacturing technology. For the other side of the problem conventional methodologies for geometry representation of CAD systems are described and their limitations with regard to AM are worked out. Finally a voxel based geometry representation is presented as a solution for computer aided geometry generation of high complex AM–structures.

Hybrid Manufacturing with Additive Manufacturing - Deppe, G.; Lindemann, C. (CECIMO Magazine)
Additive Manufacturing provides an outstanding technological and economic potential for a wide range of industries. Particularly in the field of small series production with many product variants, the technology offers decisive advantages, such as reducing component weight, functional integration, complex parts or individualization. Today potential users struggle with the integration of this technology in their businesses. The production costs of this technology often seem too high compared to traditionally manufactured parts and many users seem disappointed with the performance of the technology. The reasons for that are manifold, but often Additive Manufacturing is considered only as an isolated technology.

Holistic approach for industrializing AM technology - from part selection to test and verification - Reiher, T.; Lindemann, C.; Jahnke, U.; Deppe, G.; Koch, R. (Progress in Additive Manufacturing)
Even in times where additive manufacturing has a peak in media and industry interest, only few companies have already implemented this technology. Many companies struggle with the use of AM even if they have already identified the benefits of this technology for their business. Additional knowledge along the whole product development chain is necessary to succeed in implementing this technology. As all other production technologies, AM has certain strength and weaknesses which affect the suitable part candidates. Redesign or manufacturing approaches of unsuited part candidates are no very likely to be successful. In general, aspects like design rules need to be known along the product development process in order to achieve technology-based benefits during production and post-processing resulting in economic success. This paper will present a holistic approach which will assist the designer during product development and manufacturing based on an example part from the space industry. Then methodology starts with an appropriate part selection as a key parameter for the product development process. Based on the promising part candidates, deductions for the further product development process will be described. This includes approaches for functional integration as well as a methodology for the compilation of part requirements. Those are utilized for a black box methodology, ensuring a time-efficient redesign based on FEA optimization and design rules for additive manufacturing. Best practices for integrating (or in the best case avoiding) traditional technologies are discussed. Based on this, the development of industrialization and test and verification plans for production are shown. This includes the marking of parts for traceability during the whole product lifecycle for quality reasons as well as for product protection. Furthermore, production and production planning are discussed. This is followed by post-processing and testing procedures of the part. The paper will close with a detailed economic view on the topic and some deductions regarding the changes in the supply chain. The methodology itself is discussed and explained on a real sample metal part. The general methodology is discussed on the basis of the space industry but is subject to be adapted to other industries.

CLIL theory and empirical reality – Two sides of the same coin? - Rumlich, Dominik (Journal of Immersion and Content-Based Language Education)

The rich environment of CLIL classes as an ideal setting for collaborative learning - Rumlich, Dominik; Ahlers, Sabine (Collaborative learning and new media)

Markov state models from short non-equilibrium simulations—Analysis and correction of estimation bias - Nüske, Feliks; Wu, Hao; Prinz, Jan-Hendrik; Wehmeyer, Christoph; Clementi, Cecilia; Noé, Frank (The Journal of Chemical Physics)

Variational Koopman models: Slow collective variables and molecular kinetics from short off-equilibrium simulations - Wu, Hao; Nüske, Feliks; Paul, Fabian; Klus, Stefan; Koltai, Péter; Noé, Frank (The Journal of Chemical Physics)